2016
DOI: 10.1093/ageing/afw120
|View full text |Cite
|
Sign up to set email alerts
|

Older people remain on blood pressure agents despite being hypotensive resulting in increased mortality and hospital admission

Abstract: the results demonstrate that low SBP is associated with adverse events, it is possible that the pursuit of BP control at a population level may lead to over-treatment in certain groups of patients. This may result in an increased incidence of adverse events particularly in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…It might be necessary to design a variety of public policies including food reformulation to reduce sodium content and efforts to incentivise primary care providers to give priority to the management of SBP. 28 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…It might be necessary to design a variety of public policies including food reformulation to reduce sodium content and efforts to incentivise primary care providers to give priority to the management of SBP. 28 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Again, due to the design of this study, it was difficult to say for sure whether the hypotension was the responsible factor or this was due to severe illness which may be the primary reason of mortality, hospitalizations, and poor outcomes. [23]…”
Section: What Is the Threshold To Safely Control Blood Pressure In Thmentioning
confidence: 99%
“…The possible reasons for the lower incidence rate in females at an early age may be due to the positive effects of estrogen on the cerebral circulation. [17,18] In terms of ethnicity, this study showed that the majority of stroke patients were Malay (43.2%) followed by Indians 28.4% and Chinese 28.4%. Another study conducted in Malaysia about the incidence of stroke among Chinese, Malays, and Indians in multiple states shows, the proportion of Malay was much higher than Chinese followed by Indians.…”
Section: Discussionmentioning
confidence: 77%